Competing for Attention on Information Platforms: The Case of News - Tim Meyer; Anna Kerkhof; Carmelo Cennamo; Tobias Kretschmer (Center for Economic Studies and ifo Institute (CESifo), 2022)
Mainstream logic supports the idea that platforms bring large benefits to firms, especially smaller ones, by opening up access to a broader set of consumers and making firms' products easier to find. However, this argument mostly applies to transaction platforms that match consumer preferences to products. On information platforms such as social media or news aggregators, firms compete for consumer attention, not matches. We argue that consumer attention and choice in contexts such as news content are driven by the size and focus of content providers. Providers sufficiently large to be recognized by consumers and sufficiently broad in their focus to cover multiple content categories of interest to consumers are better positioned to capture a significant share of consumer attention, and thus demand, compared to smaller and more narrow competitors. We develop a simple formalization of our reasoning and find empirical support for it by exploiting a legal dispute leading to the removal of a group of German news outlets from news aggregators.
Keywords: 330; information platforms; competition for attention; consumer attention; news aggregators; news content